Knowledge transfer and the early modern university : statecraft and philosophy at the Akademia Zamojska (1595-1627) - Lepri, Valentina (Scientific and learned cultures and their institutions, 2019)
"Knowledge Transfer and the Early Modern University focuses on the teaching and cultural activities of the Akademia Zamojska, one of the most renowned universities of Central-Eastern Europe in the Early Modern Age. The Akademia Zamojska played its own part in the debate on the methodology of politics as a discipline, also offering an original contribution to the development of the concept of 'political prudence' which was to become so popular in the universities of Central Europe in this period. The institution embodied a largely successful attempt to knit up closer connections between the world of intellectual culture and that of political praxis"--